High-urgency kidney transplantation in the Eurotransplant Kidney Allocation System: success or waste of organs? : the Eurotransplant 15-year all-centre survey - Aßfalg, Volker; Morath, Christian; Krüger, Bernd (Nephrology, dialysis, transplantation, 2016)
BackgroundIn the Eurotransplant Kidney Allocation System (ETKAS), transplant candidates can be considered for high-urgency (HU) status in case of life-threatening inability to undergo renal replacement therapy. Data on the outcomes of HU transplantation are sparse and the benefit is controversial.MethodsWe systematically analysed data from 898 ET HU kidney transplant recipients from 61 transplant centres between 1996 and 2010 and investigated the 5-year patient and graft outcomes and differences between relevant subgroups.ResultsKidney recipients with an HU status were younger (median 43 versus 55 years) and spent less time on the waiting list compared with non-HU recipients (34 versus 54 months). They received grafts with significantly more mismatches (mean 3.79 versus 2.42; P < 0.001) and the percentage of retransplantations was remarkably higher (37.5 versus 16.7%). Patient survival (P = 0.0053) and death with a functioning graft (DwFG; P < 0.0001) after HU transplantation were significantly worse than in non-HU recipients, whereas graft outcome was comparable (P = 0.094). Analysis according to the different HU indications revealed that recipients listed HU because of an imminent lack of access for dialysis had a significantly worse patient survival (P = 0.0053) and DwFG (P = 0.0462) compared with recipients with psychological problems and suicidality because of dialysis. In addition, retransplantation had a negative impact on patient and graft outcome.ConclusionsFacing organ shortages, increasing wait times and considerable mortality on dialysis, we question the current policy of HU allocation and propose more restrictive criteria with regard to individuals with vascular complications or repeated retransplantations in order to support patients on the non-HU waiting list with a much better long-term prognosis.